Study of the health effects of coal mining on coal mine workers of Baluchistan - Azad, Salah Uddin (International Journal of Occupational Safety and Health, 2017)
Background: The data on coal mine workers was collected from May 2009 to April 2010.Objective:To study the health issues of coal mine workers. Methods: Two types of data were collected. Primary data was obtained through topographic survey and questionnaire while Secondary data about the health issues, medical facilities and other allied facilities of coal mine workers of Baluchistan (pakistan) were collected from; Mine& Mineral department of Quetta, hospitals and medicals facilities in coal mine fields. Three mine fields i.e. Mach, So-range-Degari, and Chamalong coal fields were selected and further subdivided as M1,M2,andM3 at Mach coal field, SD1, SD2 and SD3 at So-range-Degari and C1, C2 and C3 at Chamalong coal field. Results: The average emission of Methane (CH4), Carbon monoxide (CO), and Oxygen (O2) in coal mine fields was 11.8m3/ton, 36ppm and 14% respectively which, exceeded the permissible limits of 1-10m3/ton, 30ppm and 18%. The concentration of coal dust (Carbon and Quartz) was 4-5mg/m3 and 0.35mg/m3 respectively as against the threshold limits of 2mg/m3 and 0.05-0.1 mg/m3 for 8 hours daily and 40 hours/week. Due to high concentration of coal dust the miners experienced headache, irritation in throat, nose and eyes, drowsiness, shortness of breath, nausea, pneumoconiosis, tuberculosis, chronic obstructive bronchitis, heart problems, and other respiratory illnesses. The coal water and slurry was disposed off in an unconfined area causing contamination of drinking water leading to symptoms of indigestion and diarrhea to the miners. Conclusion: Government of Baluchistan and coal mine owners should take concrete steps to improve the adverse health impacts of coal miners.